An interview with Eben Venter: Trencherman and environmentalism in South Africa. Issue 4 (1st October 2016) - Premoli, Martin
Abstract: This interview explores the role of environmentalism – specifically as it relates to meat and agriculture – in the literature of South African writer Eben Venter. As discussed in the interview, Venter's novel Trencherman, through its envisioning of a post-apocalyptic South Africa, serves as an especially productive text for examining the interplay of colonialism and ecological violence.